2011
DOI: 10.1039/c005401c
|View full text |Cite
|
Sign up to set email alerts
|

Stimuli-responsive gels as reaction vessels and reusable catalysts

Abstract: As part of a continuing scientific challenge, a substantial effort during the past few decades has been devoted towards altering the selectivity of chemical transformations by arranging the potential reactants in a number of organized and confining media. Such systems, having features significantly different from those of isotropic solutions, include, for example, micelles, microemulsions, molecular aggregates, liquid crystals, and zeolites. Among these materials, stimuli-response gels constitute another impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
113
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 400 publications
(120 citation statements)
references
References 171 publications
1
113
0
6
Order By: Relevance
“…The current development of SRGs as catalyst support media has been recently reviewed by Diaz Diaz and co-authors [66]. Here we summarize just a few achievements.…”
Section: Overview Of Gel-based Materials By Applicationmentioning
confidence: 99%
“…The current development of SRGs as catalyst support media has been recently reviewed by Diaz Diaz and co-authors [66]. Here we summarize just a few achievements.…”
Section: Overview Of Gel-based Materials By Applicationmentioning
confidence: 99%
“…1,2 The simplicity of the procedure, the possible large scale production and wide variety in usable polymers, make electrospinning attractive for a wide range of biomedical applications such as tissue engineering, wound dressing, drug delivery and more. 3 In polymer research, much progress is being made in the area of so-called stimuliresponsive polymers [4][5][6][7] which can alter one or more properties such as e.g. morphology, strength or color upon exposure to external signals, such as pH, ionic strength or light.…”
Section: Introductionmentioning
confidence: 99%
“…This organizationo fm ultiple catalytic sites at the surface of the fibers could provide additional catalytic features, such as multivalent interactions, neighboring effects and cooperativity. [17][18][19] Several studies mentioning supramolecular gels as active mediaf or catalysis have been reported. Between them, the use of Pd II metallogelsc ontainingp yridine-based ligands as catalysts for the aerobic oxidationo fb enzoyl alcohol to benzaldehyde,a sw ell as the application of bolaamphiphilic l-proline derived low-molecular-weightg elators as basic catalysts for the Henry nitro-aldolr eaction, are two clear examples of success regardingthe use of catalytic gels both in metallo-and or-ganocatalysis, respectively.…”
Section: Introductionmentioning
confidence: 99%